Data Mapping From Food Diaries to Augment the Amount and Frequency of Foods Measured Using Short Food Questionnaires - Crowe, Michael; O'Sullivan, Michael; McNulty, Breige A.; Cassetti, Oscar; O'Sullivan, Aifric (Frontiers in Nutrition, 2018)
Collecting accurate and detailed dietary intake data is costly at a national level. Accordingly, limited dietary assessment tools such as Short Food Questionnaires (SFQs) are increasingly used in large surveys. This paper describes a novel method linking matched datasets to improve the quality of dietary data collected. Growing Up in Ireland (GUI) is a nationally representative longitudinal study of infants in the Republic of Ireland which used a SFQ (with no portion sizes) to assess the intake of ‘healthy’ and ‘unhealthy’ food and drink by 3-year old preschool children. The National Preschool Nutrition Survey (NPNS) provides the most accurate estimates available for dietary intake of young children in Ireland using a detailed 4-day weighed food diary. A mapping algorithm was applied using food name, cooking method and food description to fill all GUI food groups with information from the NPNS food datafile which included the target variables, frequency and amount. The augmented data were analysed to examine all food groups described in NPNS and GUI and what proportion of foods were covered, non-covered or partially-covered by GUI food groups, as a percentage of the total number of consumptions. The term non-covered indicated a specific food consumption that could not be mapped using a GUI food group. ‘High sugar’ food items that were non-covered included ready-to-eat breakfast cereals, fruit juice, sugars, syrups, preserves & sweeteners and ice-cream. The average proportion of consumption frequency and amount of foods not covered by GUI was 44% and 34%, respectively. Through mapping food codes in this manner, it was possible, using density plots, to visualize the relative performance of the brief dietary instrument (SFQ) compared to the more detailed food diary (FD). The SFQ did not capture a substantial portion of habitual foods consumed by 3-year olds in Ireland. Researchers interested in focusing on specific foods, could use this approach to assess the proportion of foods covered, non-covered or partially-covered by reference to the mapped food database. These results can be used to improve SFQs for future studies and improve the capacity to identify diet-disease relationships.